Projecting Financial Capability in Small Canadian Drinking Water Treatment Systems. Issue 10 (1st October 2017) - Janzen, Aaron; Achari, Gopal; Dore, Mohammed H.I.; Langford, Cooper H.
Abstract : This article determines the minimum service population for which construction and operation of drinking water treatment systems become financially viable by comparing costs with revenue. The feasibility of five solutions that have been implemented in Canada are discussed and tested for financial viability using a novel methodology. Recently published cost equations predict that drinking water treatment plants become financially viable at an estimated population of 920 for surface water sources and 360 for groundwater sources. Intersection points between the cost and revenue curves occur at considerably higher populations than predicted by the Statistics Canada–Calgary Regional Partnership cost equations, highlighting the challenges small systems face in providing drinking water in a sustainable and affordable manner. Decision makers should consider alternative solutions for drinking water supply at unviable service populations, including delivery of water via small diameter "trickle fill" distribution systems, point‐of‐entry and point‐of‐use treatment, and bottle fill stations.